A pragmatic approach to the combined effect of climate change and water abstraction on Lake Ziway water balance, Ethiopia. Issue 1 (14th December 2022) - Ashagre, Hailemariam Molla; Hatiye, Samuel Dagalo; Goshime, Demelash Wondimagegnehu
Abstract: Climate change and ongoing human activity have been threatening Ethiopia's Lake Ziway's water balance. However, few studies have been conducted to investigate the combined effects of climate change and water withdrawal on the lake's water balance using climate change and water withdrawal for irrigation. We used high-resolution multiple climate models and Representative Concentration Pathways (RCP) scenarios to assess the impact of climatic variables for two future periods: 2021–2050 and 2051–2080. Rainfall and temperature data biases were corrected using power transformation and variance scaling methods, respectively. The Hydrologiska Byråns Vattenbalansavdelning (HBV) hydrological model was employed to simulate surface inflow into Lake Ziway from the Meki and Katar sub-catchments. The FAO CROPWAT model was used to estimate the irrigation water demand of major crops grown in the study area. The results indicate that future temperatures and wet season runoff levels are expected to rise. Under the worst climate change scenario, climate change and water withdrawal from the lake for agriculture may cause the lake level to drop by 25 cm per year, resulting in a 10 km 2 surface area and 101 Mm 3 volume reductions. Therefore, implementing preventive measures, proper planning and careful monitoring of lake water use is advised. HIGHLIGHTS: Integration of multiple climate model, RCP scenarios, water abstraction, HBV hydrological and water balance model were used to evaluate Lake Ziway's water balance for impact analysis. Bias-corrected climate model output resulted in improved rainfall and streamflow simulation. Our findings indicate that the combined effect of climate change and water withdrawal affected both lake level and volume. Graphical Abstract